Work-Tools: Tablet for Inclusive Education - Ritamaria Bucciarelli; Maria Terrone; Pasquale Villari (Pensa MultiMedia, 2017)
Extensive studies conducted by a group of experienced researchers in linguistics and informatics, have shown that the language of the pathological perceptual disorientation, in the light of the syntactic theory, could provide a better understanding of these phenomena and give to the search tools and effective technologies.(Bulton,2010, p. 534-572. Experience over time has become a challenge to keep up with other European countries and even today it continues in agreement with the University of Hamburg Fakultät für Geisteswissenschaften, Sprache, Literatur, Medien I (SLM I), Institut für Deutsche Gebärdensprache und Kommunikation Gehörloser, and on the basis of the German dictionaries borns Work -Tools. It's a multifunctional software of consultation, composition, reformulation, transcription, translation in real time(Gilquin Griess, 2009. It's a tool for use both in teaching, that for the realization of professional texts and comprises: 1) a database (WT), said "linguistic corpus", for queries and analysis and reading "quantitative" data; 2) -file text, said "Human search converter", for the production, manipulation and reformulation of the word, the phrase and the text; 3) text file called "beyond language", transduction, decoding, translation; 4) a bar of writing for playing in real time.